Effect of vascular endothelial growth factor and interleukin-1β on apoptosis in endometrial cell cultures from patients with endometriosis and controls - Bilotas, Mariela Andrea (2010)
The aim of this study was to evaluate the effect of vascular endothelial growth factor (VEGF) and interleukin-1β (IL-1β) on apoptosis induced by leuprolide acetate (LA) in endometrial epithelial cell cultures from patients with endometriosis. Primary endometrial epithelial cell cultures were obtained from uterine endometrial biopsies of patients with endometriosis and control women. Endometrial epithelial cells were incubated with LA; a combination of LA and VEGF; a combination of LA and IL-1β; or in basal conditions. LA was added 3 h prior to addition of VEGF and IL-1β. After stimulation, the percentage of apoptotic cells was evaluated by the acridine orange-ethidium bromide technique and Bax expression was assessed by western blot. Treatment with LA enhanced the percentage of apoptotic cells in endometrial epithelial cells from subjects with endometriosis and control subjects. Addition of either VEGF or IL-1β after exposure to LA restored the percentage of apoptotic cells to basal levels. Moreover, treatment with LA increased Bax expression in endometrial epithelial cells from patients with endometriosis. This effect was reverted by the addition of either VEGF or IL-1β. Our results show that VEGF and IL-1β reduce apoptosis and decrease Bax expression in endometrial epithelial cells from patients with endometriosis. This study suggests that VEGF and IL-1β may protect endometriotic cells from undergoing apoptosis in addition to exerting their pro-angiogenic role.